Simultaneous Voltammetric Determination of Uric Acid, Xanthine and Hypoxanthine Using CoFe2O4/Reduced Graphene Oxide Modified Electrode - Vuong Hoan Thi Nguyen (TGC); Minh Ngoc Nguyen; Nguyen Thi Hong Trang; Thuy Le Thi Thanh; Van Hoang Cao; Tran Xuan Mau; Ho Xuan Anh Vu; Phan Thi Kim Thu; Nguyen Hai Phong; Dinh Quang Khieu (My University, 2020)
Simultaneous Voltammetric Determination of Uric Acid, Xanthine and Hypoxanthine Using CoFe2O4/Reduced Graphene Oxide Modified Electrode
Keywords: Uric Acid